Case Report: Ischaemic Stroke Presented with Hemichorea-Hemiballism - Ariobimo, Bonfilio Neltio; Puspamaniar, Vania Ayu; Nujum, Nurun; Puspitorini, Lisa (Jurnal Medis Islam Internasional, 2023)
Introduction: Movement disorders can be separated into hypokinetic disorders, which cause paucity or slowness (bradykinesia), and hyperkinetic disorders, which cause excessive, aberrant involuntary motions Less than 5% of individuals with cerebrovascular diseases presented with involuntary movement. It might be difficult to identify and diagnose hyperkinetic disorders. Case: We describe a 56-year-old man who arrived at the hospital with 5 hours of abrupt, uncontrollable movement in his right upper and lower limbs. A complete neurological evaluation revealed an uncontrolled, nonrhythmic, non-patterned, aimless, and frequently jerky movement of the right upper and lower limbs with a ballistic component that varies in amplitude and frequency. Higher psychic function and cranial nerves were normal. Chest radiography, electrocardiography were normal. Hemorrhage was ruled out by a brain non-contrast CT scan at admission. The patient was diagnosed with hemichorea-hemiballism caused by an ischemic stroke based on clinical evidence of a sudden neurological deficit of aberrant involuntary movement. After receiving medical treatment for five days, the involuntary motions stopped occurring without causing any more neurological abnormalities or weakening. Discussion: Ischemic stroke diagnosis relied on skilled clinical assessment without explicit neuroimaging. While hemiballismus is characterized by violent irregular flinging movements of the limbs brought on by contractions of the proximal muscles, hemichorea consists of continuous random, anarchic, and jerking movements involving both the distal and proximal muscles (though it is occasionally localized more distally). Conclusion : Hyperkinetic movement disorders are a rare presentation of stroke. The pathophysiology of these abnormal movements remains uncertain. Even though they are uncommon, following a stroke, aberrant motions can occur suddenly or develop gradually. Hemichorea-hemiballismus with abrupt onset should be treated as an acute stroke unless proven other causes